Irrational beliefs in secondary school students from a center for alternative basic education - Ortiz Álvarez, Omar Gibrahim (2021)
The objective of this article is to determine the differences in irrational beliefs among secondary school students from a Center for Alternative Basic Education, according to gender and age group. This is a descriptive study with a comparative descriptive design. The population was obtained through a census, and is made up of 161 students of both sexes from the first to the fourth grade of secondary school. The Albert Ellis Irrational Belief Inventory was administered. Frequencies and percentages were calculated, and the Kolmogorov-Smirnov normality test and the Mann-Whitney and Kruskal-Wallis U tests were used to test the hypotheses. The analysis showed that the differences in irrational beliefs, considering gender, are not significant at the level of p < 0.05, except for one irrational belief: dependence (U = 1.687.000; Unilateral sig. = 0.036), with a higher average rank in the male group. Likewise, the results show that, according to the age group, there are no significant differences, at the level of p < 0.05, in irrational beliefs, except problem avoidance (X2 = 7.017; Sig. = 0.030), with a higher average rank in the group of students aged 20 to 29.